study of charge exchanging in atom-atom scattering - Abed Alsattar, Mustafaa (University of Thi-Qar Journal of Science, 2012)
The adsorption of atoms on the surface and its effect on the charge transfer process in the hyper – thermal energies regime, is one of the most important subject in surface physics especially in studying the effect of electron – phonon coupling. And to study this effect due to the recoil of the adatom through out the scattering of atom from surface covered with low coverage , Anderson Hamiltonian is used which incorporates the interaction of the scattering atom with the adatom and the interaction of the adatom with the surface atoms. Since the atom is scattered from the adatom and the charge transfer happens through out resonance and quasi-resonance charge transfer. The Hamiltonian incorporates also the electron-phonon coupling interaction .The system of equations for scattered atom-adatom/ surface is treated using the wide band approximation.The system of equations are solved numerically using six-order Runge-Kutta method with the accuracy is checked at each time. The treatment is applied to real system, that is Li-K/W, since the ionization probability of the scattered atom , the occupation number of the adatom and the number of phonons on the adatom are calculated as function of all the variables that related to the treatment such as the initial energy of the scattered atom . The effects of the adatom-adatom interaction when the adatom are identical or not are investigated. In addition, it is found that the ionization process is enhanced when the adatoms are not identical.